2006
DOI: 10.1007/s00431-006-0280-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomized prospective study on the use of 2 g-IVIG or 1 g-IVIG as therapy for Kawasaki disease

Abstract: A single, 2 g/kg dose of immune globulin (IG), denoted 2 g-intravenous (IV)IG, has become a standard regimen for treating Kawasaki disease (KD) because of its highly preventive effect on coronary arterial lesions (CAL). However, IG is obtained from blood specimens, a drawback to many patients, and is also very expensive. This randomized prospective study reported here was carried out with the aim of developing a treatment regimen that would reduce the total dose of IG. The study tested two protocols (A: 2 g-IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…Доказано, что введение ВВИГ в дозе 2 г/кг однократно непрерывно в течение 8-12 ч более эффективно предупреждает формирование коронарных аневризм, чем ежедневное использование иммуногло-булина по 0,4 г/кг в течение 5 дней [10]. Доказано также преимущество дозы ВВИГ 2 г/кг по сравнению с 1 г/кг [11]. ВВИГ назначают и после 10-го дня болезни детям, у которых ранее диагноз не был поставлен, если у них продолжается немотивированная лихорадка или обнару-жены коронарные аневризмы и сохраняются показатели системного воспаления (увеличение СОЭ или СРБ) [1].…”
Section: Discussionunclassified
“…Доказано, что введение ВВИГ в дозе 2 г/кг однократно непрерывно в течение 8-12 ч более эффективно предупреждает формирование коронарных аневризм, чем ежедневное использование иммуногло-булина по 0,4 г/кг в течение 5 дней [10]. Доказано также преимущество дозы ВВИГ 2 г/кг по сравнению с 1 г/кг [11]. ВВИГ назначают и после 10-го дня болезни детям, у которых ранее диагноз не был поставлен, если у них продолжается немотивированная лихорадка или обнару-жены коронарные аневризмы и сохраняются показатели системного воспаления (увеличение СОЭ или СРБ) [1].…”
Section: Discussionunclassified
“…Finally, polyclonal antibodies from pooled human sera are currently used to treat various diseases such as Kawasaki's syndrome, Clostridium difficile colitis, respiratory syncytial virus, cytomegalovirus, chronic dysimmune neuropathies, chronic inflammatory demyelinating polyradiculo-neuropathy, and polyarteritis nodosa [56][62]. These IVIg products naturally vary in batch-to-batch potency, represent a potential risk for transmitting infectious agents, and the mechanisms of action are generally not well characterized [31].…”
Section: Discussionmentioning
confidence: 99%
“…Children fulfilling the diagnostic criteria for this acute febrile vasculitic disease receive a single dose of 2 g/kg of IVIg in combination with aspirin as standard therapy within 10 days of the onset of symptoms for prevention of coronary artery aneurysms, resulting in a significant decrease in morbidity and mortality [101][102][103][104][105][106]. It has been reported that in patients who respond to IVIg therapy, the secretion of IL-1 decreases, thus inhibiting T-cell responses to bacterial superantigens [107].…”
Section: Kawasaki Diseasementioning
confidence: 98%